Modelo de maximização de valor em um ambiente de incertezas e restrições operacionais: uma aplicação da teoria das restrições aliada a teoria de opções reais - Rochman, Ricardo Ratner (2005)
The objective of this work is to build a model of performance management for value creation through short long run actions in the company, in an environment with uncertainties. Such model is based on three theories: shareholder value creation, theory of constraints and real options. Depending on the decision-making horizon the role of the theories above is divided in the management model: short and long run. For the management of the short run, the model links and adjusts the concept of shareholder value creation, with the concept of economic profit, to the theory of constraints. As the constraints limit the value creation, all decisions made to create value would have to be linked to the restrictions of the constraints. On the other hand, the theory of the constraints does not approach the problem of the minimum return expected by the shareholders, which it is taken into consideration by the value-based management models. When putting together and adapting the two concepts, we will have the biggest possible value for the company in short run. The model deals with the long run recognizing and treating the uncertainties in the market and implementing the short run management model discussed previously. To the valuation of the flexibilities created and demanded for the theory of constraints we apply the real options theory not only to value the flexibilities but also to anticipate strategically decisions in the long run. The valuation of flexibilities in such a way allows to decide if the investment must or not be carried as well as to determine the maximum value to be paid in a negotiation for acquisition of flexibility. The use of models of real options valuation - as the binomial tree - allows the considered model to evaluate and to visualize the possible attitudes and decisions to be taken in the future as the uncertainties are resolved. Finally, we have a management model to be used in an environment with market uncertainties, which is focused to shareholder value creation - considering that the company has its performance limited by the constraints of the system - and evaluates present and potential flexibilities, as well as the value of the company in short and long run. By the aggregation and revision of the theory of constraints, real options and shareholder value creation, the model provides the steps to maximize the value of the company in the short and long run.